The Major Psoriasis Susceptibility Locus PSORS1 Is not a Risk Factor for Late-Onset Psoriasis - Allen, Michael Hugh; Ameen, Hahreen; Veal, Colin; Evans, Julie; Ramrakha-Jones, V.S.; Marsland, A.M.; David Burden, A.; Griffiths, C.E.M.; Trembath, Richard C.; Barker, Jonathan N.W. N. (Journal of investigative dermatology, 2005)
PSORS1 is the major susceptibility locus for psoriasis vulgaris (PV) and lies within an approximately 200 kb segment of the major histocompatibility complex on chromosome 6p21.3. Alleles of candidate genes in this region including human leukocyte antigen (HLA)-C, α-helical coiled coil rod (HCR), and corneodesmosin (CDSN) show association with early-onset PV. Late-onset psoriasis (LOP) is defined as a disease with onset after 40 y of age and is typically sporadic. We assessed the role of PSORS1 in genetic susceptibility to LOP. Genotyping for HLA-C alleles and seven single nucleotide polymorphisms (SNP) within the genes HCR and CDSN was performed in LOP (n=145) and normal controls (n=309). Statistical analysis of allelic frequencies included calculation of odds ratio and χ2 comparisons. LOP demonstrated only a weak association to PSORS1 alleles HLA-Cw*6 (p=0.037), CDSN*5 (p=0.041), HCR*WC (p=0.013), and HCR SNP +325 (p=0.038). Patients with age of onset for psoriasis of 50 y or above provided no evidence of association with any of these alleles. These data suggest that the study cohort may include a number of subjects who harbor PSORS1 predisposition to early-onset psoriasis and yet do not present with disease by the age of 40 y. Thus this study demonstrates that PSORS1 is not a major inherited risk factor in the pathogenesis of LOP. These data suggest that the exclusion of LOP subjects from case–control studies will aid further delineation of the PSORS1 locus. Future genome-wide studies will be required to identify loci conferring risk for late-onset disease.